Evaluation of a School—Juvenile Court Team Approach to Delinquency Prevention - Lindsey, Elizabeth W. (Children and youth services review, 1987)
The School-Juvenile Court Liaison Project was designed to assist schools and courts in working cooperatively to intervene in and prevent delinquency. Results of the evaluation indicate increased communication and joint service planning between the systems. School and court personnel are talking to each other more often about students who are involved with the court, as well as about general issues of school-court cooperation, and school and court staff are working together more frequently to develop treatment plans for such students. School-court teams have also been successful in developing interagency case staffing councils and prevention-oriented projects in their communities. Factors contributing to the project's success are discussed